Motion Detection by Microcontroller for Panning Cameras - Benito-Picazo, Jesús; López-Rubio, Ezequiel; Ortiz-de-Lazcano-Lobato, Juan Miguel; Domínguez-Merino, Enrique; Palomo-Ferrer, Esteban José (My University, 2017)
Motion detection is the first essential process in the extraction of information regarding moving objects. The approaches based on background difference are the most used with fixed cameras to perform motion detection, because of the high quality of the achieved segmentation. However, real time requirements and high costs prevent most of the algorithms proposed in literature to exploit the background difference with panning cameras in real world applications. This paper presents a new algorithm to detect moving objects within a scene acquired by panning cameras. The algorithm for motion detection is implemented on a Raspberry Pi microcontroller, which enables the design and implementation of a low-cost monitoring system.
Keywords: Teledetección; foreground detection; background modeling; probabilistic self-organizing maps; background features